Recent Advances in Swarm Mobile Robotics - Santos, Lyndaines Araujo; Macêdo Maia, Saulo; Guimarães Batista, Josias; Soeiro, Renan Rabelo; Lins de Macedo, Antonio Roberto; Costa de Albuquerque, Victor Hugo (Journal of Mechatronics Engineering, 2024)
This paper is a critical analysis of the recent advances in the field of swarm mobile robotics. The aim of this article is to analyze the latest developments and technologies being applied in this field. The Science Direct and IEEEXplore data bases were searched for relevant articles published from 2014 to 2020. The selected articles which refer to swarm robotics were individually analyzed to identify their objectives, methodology and results. Although this analysis demonstrates the main areas of advancement, there are some aspects which make the replication and comparison of the proposed techniques difficult, such as the non-standardization of simulation tools and the non-existence of public data bases for certain kinds of application. However, the studies show potential for applications in real environments and based on this analysis, several techniques and tools, used in recent studies concerning swarm robotics are highlighted here.